2018
DOI: 10.1163/15685403-00003847
|View full text |Cite
|
Sign up to set email alerts
|

Effects of algae, yeast and photosynthetic bacteria diets on survival and growth performance in the fairy shrimp, Streptocephalus sirindhornae (Branchiopoda, Anostraca)

Abstract: This study investigated the effects on survival, growth performance and water quality of algae, yeast and photosynthetic bacteria as diets for larval and immature/mature Streptocephalus sirindhornae. Survival of the larvae fed with the alga Chlorella vulgaris and the photosynthetic bacterium Rhodopseudomonas faecalis for 5 days was higher than 80%, while those fed with the yeast Saccharomyces cerevisiae was 4.4%. After feeding the 6-day-old fairy shrimp until they reached 30 days of age, those fed with bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Previous study has reported that this bacterium can be utilized as diet in the freshwater fairy shrimp Streptocephalus sirindhornae. Not only did it enhance survival rate and growth performance of the fairy shrimp but it also reduced ammonia, nitrite, and nitrate concentrations of the water compared to those fed with the alga Chlorella vulgaris and the yeast Saccharomyces cerevisiae (Saejung, Chaiyarat, & Sa-noamuang, 2018). These findings suggest that this strain is a good candidate as SCP for animal feed.…”
mentioning
confidence: 83%
“…Previous study has reported that this bacterium can be utilized as diet in the freshwater fairy shrimp Streptocephalus sirindhornae. Not only did it enhance survival rate and growth performance of the fairy shrimp but it also reduced ammonia, nitrite, and nitrate concentrations of the water compared to those fed with the alga Chlorella vulgaris and the yeast Saccharomyces cerevisiae (Saejung, Chaiyarat, & Sa-noamuang, 2018). These findings suggest that this strain is a good candidate as SCP for animal feed.…”
mentioning
confidence: 83%
“…>51%) could be indicative of the suitability of Haematococcus sp. as feed for B. orientalis , as previously reported in the feeding of Streptocephalus sirindhornae with various diets including Chlorella vulgaris , Saccharomyces cerevisiae , and Rhodopseudomonas faecalis [ 74 ]. However, their proportions varied among different treatments mainly due to changes in the protein metabolism or energetic status of the organism [ 72 ].…”
Section: Discussionmentioning
confidence: 69%
“…RP can provide protein, lipids, essential amino acids, essential fatty acids, vitamins and carotenoids [59][60][61][62][63], which can be used as a substitute for feed ingredients [64]. Feeding RP increases the growth and survival of fairy shrimp (Streptocephalus sirindhornae) [65]. Saejung et al reported that three types of anaerobic RP increased the growth and survival of S. sirindhornae [66].…”
Section: Induction Of Amps By Feed Supplementation With Different Str...mentioning
confidence: 99%